2001
DOI: 10.1016/s1097-2765(01)00353-7
|View full text |Cite
|
Sign up to set email alerts
|

A Unique PPARγ Ligand with Potent Insulin-Sensitizing yet Weak Adipogenic Activity

Abstract: FMOC-L-Leucine (F-L-Leu) is a chemically distinct PPARgamma ligand. Two molecules of F-L-Leu bind to the ligand binding domain of a single PPARgamma molecule, making its mode of receptor interaction distinct from that of other nuclear receptor ligands. F-L-Leu induces a particular allosteric configuration of PPARgamma, resulting in differential cofactor recruitment and translating in distinct pharmacological properties. F-L-Leu activates PPARgamma with a lower potency, but a similar maximal efficacy, than rosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(213 citation statements)
references
References 42 publications
6
207
0
Order By: Relevance
“…One of the first SPPARgMs that was tested, and which validated this idea, is FMOC-l-Leucine (F-lLeu), which separates insulin sensitivity from adipogenesis in vivo [232].…”
Section: Selective Pparg Modulators: a Better Alternative?mentioning
confidence: 99%
“…One of the first SPPARgMs that was tested, and which validated this idea, is FMOC-l-Leucine (F-lLeu), which separates insulin sensitivity from adipogenesis in vivo [232].…”
Section: Selective Pparg Modulators: a Better Alternative?mentioning
confidence: 99%
“…However, treatment did not cause significant body weight gain nor marked increases in mRNA levels of PPAR␥-regulated adipocyte-ADRP and LPL genes, which are involved in lipid uptake and storage in adipose tissue, in contrast to pioglitazone. It has been suggested that Fmoc-L-leucine, a potent insulin-sensitizing compound, acts as a selective PPAR␥ modulator and improves insulin resistance in diabetic mice despite only marginally inducing adipocyte-ADRP and LPL gene expression in adipose tissue (28). It should be noted that treatment with this compound also had no effect on body weight.…”
Section: Isohumulones Up-regulated the Expression Of Genes Involved Imentioning
confidence: 99%
“…From day 3 on, cells were incubated with DMEM, 10% serum, 10 mg/ml insulin, and 10 À6 m rosiglitazone when stated. Oil-red-O staining is described elsewhere (Rocchi et al, 2001). Human colon adenocarcinoma CaCo2 and HT-29 cells (ATCC) were grown in Mc Coy's medium supplemented with 10% FCS.…”
Section: Cell Culture Protein Extracts and Transfectionsmentioning
confidence: 99%